2004
DOI: 10.1590/s1516-89132004000300012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host availability and egg load in Trichogramma platneri Nagarkatti (Hymenoptera: Trichogrammatidae) and its consequences on progeny quality

Abstract: Experiments were conducted to determine whether

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
0
5
0
7
Order By: Relevance
“…1), but did not differ in the number of eggs deposited per larva (Table 1), which are correlated biological parameters. At the lowest density, possibly, this event is the result of a female strategy to avoid superparasitism, as this could affect the development of the offspring due to intraspecific competition for food resources (Hohmann and Luck 2004;Varaldi et al 2005;Chen et al 2006;Silva-Torres et al 2009b). Females of B. vulgaris, after evaluating the physiological condition of the host larva, may reduce the number of eggs deposited per host (2.6 ± 0.49 eggs/48 h), similar to that reported by Carvalho et al (2002) who found an average of 1.2 (± 0.21) eggs/for B.vulgaris parasitizing boll weevil larvae.…”
Section: Discussionmentioning
confidence: 99%
“…1), but did not differ in the number of eggs deposited per larva (Table 1), which are correlated biological parameters. At the lowest density, possibly, this event is the result of a female strategy to avoid superparasitism, as this could affect the development of the offspring due to intraspecific competition for food resources (Hohmann and Luck 2004;Varaldi et al 2005;Chen et al 2006;Silva-Torres et al 2009b). Females of B. vulgaris, after evaluating the physiological condition of the host larva, may reduce the number of eggs deposited per host (2.6 ± 0.49 eggs/48 h), similar to that reported by Carvalho et al (2002) who found an average of 1.2 (± 0.21) eggs/for B.vulgaris parasitizing boll weevil larvae.…”
Section: Discussionmentioning
confidence: 99%
“…atopovirilia necessita de carboidratos e a ausência de alimento interfere na longevidade e fecundidade desse parasitóide. O período sem o hospedeiro também interfere na capacidade reprodutiva desse parasitóide, pois, à medida que as fêmeas ficam sem receber ovos do hospedeiro aumenta a taxa de retenção dos ovos nas fêmeas (Hegazi et al, 2000, Reznik et al, 2001) e afetam a qualidade de sua progênie (Hohmann & Luck, 2004).…”
Section: Discussionunclassified
“…Estudos com diferentes insetos têm mostrado que organismos que investem mais em reprodução podem ter redução na longevidade como resultado de um balanço energético entre reprodução e sobrevivência (Reznick 1985, Bell & Koufopanou 1986, Stearns 1992. Apesar de existir pouca evidência da existência desse balanço em Hymenoptera Parasitica, Hohmann & Luck (2004) (Liu et al 1997), diferentemente da linhagem do Agreste de Pernambuco, que não deve apresentar quiescência devido à baixa variabilidade das condições climáticas durante o ano, e também pelo fato de ser constatado parasitismo de P. xylostella em todas as estações, indicando possíveis diferenças de estratégia de vida entre linhagens.…”
Section: Discussionunclassified
“…O fator que determina a eficiência de um parasitóide está intimamente ligado à sua capacidade de encontrar o hospedeiro em campo, manipular o número de ovos a serem depositados por hospedeiro e sua sobrevivência, em resposta à disponibilidade de hospedeiros. Nessas condições, o estado fisiológico do parasitóide tem implicações importantes para seu sucesso reprodutivo (Hohmann & Luck 2004).…”
unclassified
See 1 more Smart Citation